IMPLEMENTASI SISTEM PEJAMINAN MUTU INTERNAL SEBAGAI UPAYA PENINGKATKAN MUTU DI PERGURUAN TINGGI - Neng Wardah Ramadaniatul Millah; Siti Nur Rahmawati Shafariah; Lisani Yanuarti Solihatussajida (Program Studi Manajemen Pendidikan Islam, 2023)
This study aims to describe the implementation of the Internal Quality Assurance System (SPMI) as an effort to improve the quality of education at Djuanda University. This study is a qualitative research with a case study method. The research was conducted at Djuanda University, with the subject of the Quality Assurance and Institutional Development Agency (BPMPI). Data collection techniques: direct observation, search of documents and archives, and interviews. The results showed: (1) SPMI's policies and concepts in the form of academic documents and quality documents were prepared by BPMPI; (2) BPMPI as coordinator in planning and implementing SPMI at Djuanda university; (3) SPMI implementation is carried out by drafting the SPMI Cycle (PPEP); (4) Obstacles faced: leadership commitment, number of auditors, SPMI activities become routine; (5) Steps taken: providing quality assurance experts, training auditors, building a spirit of quality assurance; (6) SPMI Implementation Evaluation is carried out every year; (7) Utilization of SPMI implementation results: building a culture of quality, national and international accreditation and certification; and (8) SPMI implementation development refers to ISO quality management and BAN PT standards